2004
DOI: 10.1128/jb.186.5.1430-1437.2004
|View full text |Cite
|
Sign up to set email alerts
|

TeiR, a LuxR-Type Transcription Factor Required for Testosterone Degradation inComamonas testosteroni

Abstract: We have identified a new steroid-inducible gene (designated teiR [testosterone-inducible regulator]) inComamonas testosteroni that is required for testosterone degradation. Nucleotide sequence analysis of teiR predicts a 391-amino-acid protein which shows homology between residues 327 and 380 (C-terminal domain) to the LuxR helix-turn-helix DNA binding domain and between residues 192 and 227 to the PAS sensor domain. This domain distribution resembles that described for TraR, a specific transcriptional regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 42 publications
1
31
0
1
Order By: Relevance
“…Most of the genes in this cluster are involved in aromatization and following degradation of the A-ring in steroid degradation [14] (Figure 11). testosteroni [17,[67][68][69]. This transcriptional regulator is a LuxR family protein and possesses helix-turn-helix motif at the C-terminal to bind DNA.…”
Section: -6 Aromatization Of the A-ring Accompanied By The Cleavagementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the genes in this cluster are involved in aromatization and following degradation of the A-ring in steroid degradation [14] (Figure 11). testosteroni [17,[67][68][69]. This transcriptional regulator is a LuxR family protein and possesses helix-turn-helix motif at the C-terminal to bind DNA.…”
Section: -6 Aromatization Of the A-ring Accompanied By The Cleavagementioning
confidence: 99%
“…This transcriptional regulator is a LuxR family protein and possesses helix-turn-helix motif at the C-terminal to bind DNA. It is an activator which induces 3,17-hsd, 3-hsd, ksi, TesA2 to ORF18-encoded enzyme, TesA1 to TesG, SteA to ORF6-encoded enzyme, the meta-cleavage enzyme and the ORFs in the downstream DNA region [17,67] Homology search for putative steroid degradation genes in the genomic sequence data on the web using deduced amino acid sequences of tesB to ORF33 revealed the presence of putative steroid degradation gene clusters similar to tesB to ORF33 in bacteria of different genera. Among a number of candidate bacteria, ten strains of seven genera were selected for comparison (C. testosteroni CNB-1 [29], C. testosteroni KF1 (draft sequence, accession: NZ_AAUJ02000001) [70,71], Cupriavidu necator (formally R. eutropha) JMP134 (accession: NC_007347) [72,73], Ralstonia eutropha H16 (accession: NC_008314) [74], Burkholderia cenocepacia J2315 (accession: NC_011001) [75], Burkholderia sp.…”
Section: -6 Aromatization Of the A-ring Accompanied By The Cleavagementioning
confidence: 99%
“…Cloning of the teiR Gene from C. testosteroni and Subcloning of teiR Gene Fragments-The teiR gene was cloned from C. testosteroni (ATCC 11996) chromosomal DNA by using the following pair of primers: forward primer 5Ј-CGAGCTCCAT-CGCTTGCGTG-3Ј and reverse primer 5Ј-GCGGCCGCTCT-ATGCCCG-3Ј (30). The full teiR gene was then cloned into pCR2.1-TOPO to yield plasmid pTOPO4, which after sequence confirmation (MWG) was used as template for further PCR reactions (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Repressor B (RepB) turned out to bind to the mRNA of 3␣-HSD/CR, thereby interfering with hsdA translation (29). By transposon mutagenesis, teiR (testosterone-inducible regulator) was identified, a gene that was hypothesized to encode a positive regulator of steroid degradation in C. testosteroni ATCC11996 in the presence of testosterone (30). A similar positive regulator (TesR) was cloned and postulated to regulate a steroid degradation gene clusters in C. testosteroni TA441 (14).…”
mentioning
confidence: 99%
“…To elucidate the pathogenesis of APEC, we adapted signature-tagged transposon mutagenesis to a 5-week-old chicken model and identified 28 virulence-associated genes (Li et al, 2005). Among them, yjjQ encodes a putative transcriptional regulator since sequence analysis revealed that it harbours a helix-turn-helix (HTH) DNA-binding domain shared by all members of the LuxR family regulators (Chirwa & Herrington, 2003;Crater & Moran, 2001;Pruneda-Paz et al, 2004). The presence of yjjQ has been reported for commensal and various pathogenic bacteria such as enterohaemorrhagic E. coli (EHEC), uropathogenic E. coli (UPEC), Shigella and Salmonella by genomic sequencing.…”
Section: Introductionmentioning
confidence: 99%